School-based Training for Novice Teachers in Vocational Colleges - LUO , Qi (Journal of Social Science Studies, 2022)
With the development of the new era, Chinese society needs more high-quality workers, and puts forward new requirements for the high-quality development of vocational education. In order to ensure the sound development of vocational education, the key is to improve the professional level of teachers in Vocational Colleges through school-based training, especially school-based training for novice teachers from the aspects of teachers' morality, theoretical teaching, practical teaching and so on.